Designing pedestrian roads on campus: The female students’ colleges at the University of Hail as a model - Al-Saif, Eman Abdulaziz (Journal of Humanities & Social Sciences, 2024)
Pedestrian map application fields are diverse, including study and work trips, as well as recreational trips. While people can use a wide range of devices to orient themselves, furthermore, it is easy to find the fastest route from one location to another by using popular route applications, for instance Google, however, pedestrian navigation systems are impacted by a general lack of road networks, for example, navigating within some areas such as the campus is challenging because the road networks do not include pedestrian paths. As a result, using existing road networks at universities to aid pedestrians is insufficient and inactive. The aim of this study is to present the concept of pedestrians, the pedestrian network, and a pedestrian map will also be designed to support users in finding their way within the campus of the Women's Colleges Campus at the University of Hail. The pedestrian network was mapped using the descriptive method and applied technique in this study.  The results show the creation of a pedestrian network by using manual satellite image digitizing. The study revealed some shortcomings, including the need for information for barrier-free pathways for wheelchair users, clarifying obstacles such as stairs, and improving accessibility wheelchair users to university facilities. The study also recommended the development of mobile applications for pedestrian navigation based on the built pedestrian network.
Keywords: Network; Pedestrian Map; Geographic Database; Campus; Manual Digitizing; Network Analysis